The millipede family Metopidiotrichidae new to the fauna of Taiwan: the description of a new species; a review of and a key to the Chordeumatida occurring in Taiwan (Diplopoda) - Mikhaljova, Elena V.; Golovatch, Sergei I.; Chang, Hsueh-Wen (Zootaxa, 2011)
The family Metopidiotrichidae and the genus Metopidiothrix Attems, 1907 are formally new to the fauna of Taiwan, due to the discovery of Metopidiothrix taiwanensis sp. nov. The fauna of Chordeumatida of Taiwan is reviewed and keyed, at present containing 13 unquestioned species from three genera and three families. Three further species, one genus and one family are dubious either as taxa or as elements of the Taiwanese fauna, or both. Palaearctic elements, such as Diplomaragnidae and Niponiosomatidae, appear to strongly dominate over austral/tropical ones (Metopidiotrichidae).